Efficacy of B - mode and elastography ultrasound technique in the prediction of Helicobacter pylori: a prospective study - Abdulaziz Hussein; Awadia Gareeballah; Amin Mohsen Amer; Sultan Abdulwadoud Alshoabi; Moawia Gameraddin; Maisa Elzaki; Walaa Alsharif; Fahad H. Alhazmi; Raga Ahmed Abouraida; Kamal Alsultan; Fathelrehman Ahmed Elajab; Mohamed Adam (BMC Gastroenterology)
Abstract Background Helicobacter pylori (HP) affect nearly 50% of the world’s population and can colonize the submucosal and mucosal layers of the stomach wall, causing inflammation leading to a thickening of these layers. The study aimed to evaluate the application value of transabdominal ultrasonography combined with elastography in the prediction of HP using HP Fecal Antigen Test as gold standard. Method This prospective case-control study was conducted in 174 participants classified into three groups: Group A: Symptomatic patients with thickened stomach antral and evident HP infection on fecal antigen test results, Group B: Symptomatic patients with thickened antral and no evident HP infection on fecal antigen test results, and Group C: control group of asymptomatic individuals with negative HP screening to predict the diagnostic accuracy of B-mode ultrasound and elastography in the prediction of HP pylori. Results Positive HP patients had higher values of antral wall thickness (AWT), mucosal layer thickness (MLT), MLT/AWT ratio, SR (strain ratio), and a combination of AWT and SR: 5.57 ± 0.55 mm, 2.96 ± 0.45 mm, 0.53 ± 0.06 mm, 3.21 ± 0.43, and 8.79 ± 0.68 mm, respectively. In comparison, negative HP patients had values of 4.61 ± 0.47 mm, 2.05 ± 0.42 mm, 0.41 ± 0.08 mm, 2.51 ± 0.42 mm, and 7.13 ± 0.62 mm, respectively, and the control groups had values of 3.53 ± 0.36 mm, 1.47 ± 0.25 mm, 0.40 ± 0.06 mm, 1.81 ± 0.41, and 5.35 ± 0.55 mm, respectively (p < 0.001). The sensitivity of B-mode ultrasonography, elastography, and the combination of the two was 98%, 95.1%, and 98.4%, respectively, and the diagnostic accuracy was 98.4%, 98.3%, and 100%, respectively. Conclusion B-mode ultrasonography and elastography exhibit high discriminatory power in distinguishing symptomatic HP patients from normal individuals and differentiating + HP from - HP, with greater discriminatory power when combined both modes.